Hubungan Faktor Sanitasi, Ibu, dan Ekonomi Keluarga dengan Kejadian Stunting pada Balita di Puskesmas Sungai Tering Kabupaten Tanjung Jabung Timur - Windra, Dony; Kalsum, Ummi; Syarifuddin, Hutwan (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Stunting can be caused by direct and indirect factors. The aim of the study was to determine the factors associated with the incidence of stunting in toddlers in the working area of the Sungai Tering Public Health Center, East Tanjung Jabung Regency.The type of the research is cross sectional study. Data was collected in the working area of the Sungai Tering Community Health Center, East Tanjung Jabung Regency, with a total sample of 157 toddlers aged 24-59 months. The variables studied are environmental sanitation, maternal, and family economy factor. Stunting was measured by TB/U (Height-for-age) < -2 SD, Chi-Square analysis and logistic regression.The proportion of stunting under five is 26.1%. There is a relationship between enviromental sanitation that is house conditions, mother factor that are knowledge and parity with stunting. There is no correlation between economics factor with stunting. The dominant factor is the age of the mother during pregnancy who was relatively young (<20 years) (POR 6.04; 95% CI 0.77-47.19) after controlling for the variables of clean water facilities, house conditions, mother's knowledge, age of first mother married, parity , spacing of pregnancies, and family income. Maternal age during pregnancy <20 is the dominant factor causing the risk of stunting. It is recommended that people avoid early marriage and if it has already happened, it is best to postpone pregnancy with contraception until the ideal gestational age is > 20 - < 35 years.